(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2015)
The purpose of this study was to show the antidiabetic effect of ethanolic extract of Aloe vera gel in alloxan induced hyperglycaemic mice. Ethanolic extract of Aloe vera gel was orally administered for four weeks at a dose of 300mg/kg body weight. Weekly estimates of fasting blood glucose level in normal non-diabetic and alloxan induced hyperglycaemic mice were assessed. Ethanolic Aloe vera gel extract revealed no blood glucose lowering action upon non-diabetic mice. But, a significant reduction in blood glucose level (p<0.001) was seen in diabetic mice, when compared with diabetic control. Similar results were found when compared with a standard antidiabetic drug, gliclazide. To conclude, as administration of ethanolic extract of Aloe vera gel significantly reduces blood glucose level in hyperglycaemic mice, it can optimistically emerge as a new hope in the management of diabetes mellitus. DOI: http://dx.doi.org/10.3329/bjpp.v30i2.22680 Bangladesh J Physiol Pharmacol 2014; 30(2): 25-31